Pengelolaan Desain Dan Pesan Persuasif Pada Media Promosi Sekolah - Mukaromah Mukaromah; Dzuha Hening Yanuarsari; Mutia Rahmi Pratiwi (STKIP Andi Matappa, 2021)
Management of promotional media is important for schools to attract the attention of stakeholders. Problems that arise in media management are limited competent resources and limited funds owned by the school. MI Baiturahim and MI Al Hikmah Semarang City are two schools in Semarang City that are still limited in managing promotional media. This community service activity was carried out for two days to meet the needs of school partners related to training in understanding persuasive communication and practical design tools for teachers as managers of school promotion media. The method of implementing activities is through FGD (Forum Group Discussion) which takes place before until the end of the activity, the delivery of theoretical material related to persuasive communication and classification of promotional media, and the practice of using Photoshop design tools. The results of the evaluation of the activities were an increase in the understanding of training participants related to conceptual communication, classification of promotional media and increasing teacher competence in applying design software in the form of Photoshop.